The effect of working memory updating training on the Chinese writing ability of primary school students - Gao, Jiacheng; Li, Guangxin; Yang, Zimo; Li, Fengjuan; Wang, Tian; Wen, Suxia (Frontiers in Psychology, 2023)
OBJECTIVE: This study aimed to explore the effects of working memory updating training on primary school students' writing ability and performance. METHODS: Forty-six fourth-grade Chinese primary school students were recruited; their performance in the Chinese character N-back training task, the Writing Ability Questionnaire, and a time-limited writing task was assessed. RESULTS: The paired-sample t-test revealed that working memory updating training significantly improved the experimental group’s working memory level. After training, a repeated-measures ANOVA revealed that the experimental group's performance on the Writing Ability Questionnaire improved and was higher than that of the control group. In the time-limited writing task, independent-sample t-tests revealed that the experimental group’s writing fluency increased and was higher than that of the control group, while the latter’s grammatical accuracy and complexity decreased and were lower than those of the former. CONCLUSIONS: Working memory updating training can be used as auxiliary cognitive training to improve primary school students' working memory level, thereby promoting their writing development.